Factors influencing physical activity behavior in older adults with subjective cognitive decline: an empirical study using SEM and fsQCA methods - Li, Wei; Hong, Sixue; Chen, Yiping; Zhao, Yang; Wang, Limei (Frontiers in Public Health, 2024)
Objectives: Despite the evident potential benefits of engaging in physical activity (PA) for older adults with subjective cognitive decline (SCD), their PA levels remains low. Previous research has predominantly focused on PA behaviors in individuals with dementia/mild cognitive impairment, with limited attention given to those with SCD. Therefore, this study aims to identify key factors influencing PA behavior in older adults with SCD based on the Self-Determination Theory (SDT) and the capability-opportunity-motivation (COM-B) model. Methods: Three hundred and three individuals aged 60 and above with SCD participated in this study. A face-to-face structured questionnaire survey was conducted. Data were analyzed using Structural Equation Modeling (SEM) and Fuzzy Set Qualitative Comparative Analysis (fsQCA). Results: SEM results indicate that PA social support primarily influences PA behavior through three indirect pathways: the separate mediating effect of basic psychological needs, the separate mediating effect of motivation, and the chained mediating effect of both. Physical literacy, on the other hand, influences PA behavior through the separate mediating effect of motivation. Necessary conditions analysis by fsQCA reveals that no single factor is necessary for promoting PA behavior in older adults with SCD, while sufficiency analysis identifies four different combinations of factors leading to PA behavior. Conclusion: The model derived from the framework of SDT and the COM-B model effectively explains and predicts the interrelationships among variables. Physical activity behavior in older individuals with SCD is the result of multifactorial synergies.